Tantangan sosial-ekonomi pengangguran usia muda di Indonesia - Ningrum, Vanda (Jurnal Kependudukan Indonesia, 2013)
The population projections conducted by BPS and UNDP shows that by 2025 there will be an increase in the population of productive age to become 187.6 million. In this condition, the dependency ratio of Indonesia's population will be in the lower position and demographically can be regarded as the demographic bonus. This has implications for the importance of the creation of productive employment opportunities. If these conditions cannot be achieved, it will lead to an increase in youth unemployment which will bring an impact on the socio-economic conditions of a nation. In Indonesia youth unemployment rate rose from 53.6 percent in 2008 to 56 percent and is projected to increase even more if there are not any policies that support youth employment. The unemployed mostly live in urban areas and own middle and upper levels of education. This paper aims to analyze the long-term socio-economic challenges due to the high number of unemployed youth in Indonesia. The method used is the descriptive analysis as well as the literature using a variety of data and statistics from the World Bank, ILO, and BPS. The analysis shows that in the long run, the high rate of youth unemployment will cause Indonesia to face many challenges such as; first, the diminution in terms of human capital and social, mental and physical health, the declining of income and consumption, as well as the decrease in the involvement in political democratization. And second the increased risk of suicide and crime in urban areas.